2019
DOI: 10.1073/pnas.1815515116
|View full text |Cite
|
Sign up to set email alerts
|

Blocking CXCR4 alleviates desmoplasia, increases T-lymphocyte infiltration, and improves immunotherapy in metastatic breast cancer

Abstract: Metastatic breast cancers (mBCs) are largely resistant to immune checkpoint blockade, but the mechanisms remain unclear. Primary breast cancers are characterized by a dense fibrotic stroma, which is considered immunosuppressive in multiple malignancies, but the stromal composition of breast cancer metastases and its role in immunosuppression are largely unknown. Here we show that liver and lung metastases of human breast cancers tend to be highly fibrotic, and unlike primary breast tumors, they exclude cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
258
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 300 publications
(274 citation statements)
references
References 60 publications
15
258
0
1
Order By: Relevance
“…Despite the success of targeting the stromal compartment in tumors (7,11,15,19,20,41), in particular tumor ECM, there are still a series of challenges that remained to be addressed. In the first part of this study we tackle two of these challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the success of targeting the stromal compartment in tumors (7,11,15,19,20,41), in particular tumor ECM, there are still a series of challenges that remained to be addressed. In the first part of this study we tackle two of these challenges.…”
Section: Discussionmentioning
confidence: 99%
“…In cholangiocarcinoma, an immune mesenchymal subtype has been identified, which is associated with TGF signature and poor tumor infiltrating cells (18). Other axes including the CXCR4/CXCL12 in breast metastasis and the focal adhesion kinase in pancreatic ductal adenocarcinoma (PDAC) have also been associated with both desmoplasia and absence of cytotoxic T lymphocytes in tumors from mice (19). Consequently, the inhibition of these axes in preclinical mouse cancer models was shown to reduce fibrosis while significantly increasing T cell infiltration and improving response to checkpoint inhibitors (7,16,20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Vessel compression is a result of mechanical forces accumulated within stroma components of tumors (21)(22)(23). Indeed, our previous studies (24)(25)(26) showed that inhibiting CXCL12/CXCR4 or angiotensin signaling can target cancer-associated fibroblasts (CAFs) and extracellular collagen and hyaluronan, which in turn alleviates intratumoral forces, decompresses tumor vessels, and improves perfusion as well as the outcome of ICBs. We have referred to this approach as stroma normalization (27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Stroma and vascular normalization improve tumor perfusion and oxygenation and can enhance immune response by skewing TAM polarization toward the M1 phenotype, which is tumoricidal and immunostimulatory (10,13,24,39,40). This can also result in the activation of dendritic cells, cytotoxic T lymphocytes, and natural killer (NK) cells (39).…”
mentioning
confidence: 99%
“…Recent studies also suggest the use of CXCR2 or CXCR4 inhibitors in combination with immunotherapy to overcome therapeutic resistance. 82,88 These novel therapeutic strategies, together with the use of the new predictive tools based on clock genes expression for cancer prognosis will lead to a precision circadian medicine with improved efficacy and immunotherapy responsiveness. 39,89 In conclusion, our study provides for the first time experimental evidence of the link between CRD and an increase in cancer cell dissemination and metastasis formation.…”
Section: Discussionmentioning
confidence: 99%